Requests Politeness Strategies in Algerian Learners of English Academic Emails - ATAMNA, Elkhiar (Journal of Human Sciences, 2016)
How politeness is perceived in different languages and cultures is still a matter of controversy among linguists. There seems to be little agreement on what is polite/impolite in different languages and cultures. The situation is even more aggravated when it comes to foreign language learners. Because of their reliance on their native language/culture sociopragmatic and pragmalinguistic knowledge, many of them transfer their first language rules of politeness into the foreign language. This article is an attempt to examine the Algerian advanced learners of English notions of (in)directness strategies and politeness in the speech act of requests and to demonstrate that many of them fuse their native politeness conventions with those of English. This is mainly attempted through the analysis of their academic emails to their supervisors. The results showed that there is a correlation between complexity/simplicity of request strategies and the learners’ level of language proficiency and that the learners’ perception of politeness is influenced by their culture.